SUSTAINABLE DEVELOPMENT OF INDUSTRIAL ENTERPRISES IN CONDITIONS OF ECONOMIC INSTABILITY - M. Ya. Veselovsky; A. V. Fedotov; D. S. Volchkov (Модернизация, инновация, развитие, 2016)
In article the perspective of a sustainable development of the industrial enterprises is investigated, the factors infl uencing stability of development of the enterprises are analyzed, defi nition of different types of economic stability in the period of economic instability is given, internal and external factors of stability of the enterprises are allocated, is underlined that economic stability, first of all, is distinguished from the major factors infl uencing stability of development of the industrial enterprises. At the same time, authors consider factors of the available instability and their infl uence on rates of development of the industrial enterprises. Change of the current situation requires weakening of a number of the factors resulting in economic instability.Purposes. The purpose of article is the analysis of factors of the industrial enterprises infl uencing a sustainable development in the conditions of economic instability and development of the off ers providing on their sustainable development. Article tasks: to investigate and allocate factors, in the conditions of the worsening economic situation which are expedient for considering at a solution of the problem of a sustainable development of the industrial enterprises.Methodology. When carrying out the real research materials of the state statistics were the main sources of basic data. Comparative methods of the analysis are the basis for methodical development.Results. The concept is given and types of economic stability of the industrial enterprises are given. Infl uence of internal and external factors of the enterprises infl uencing stability is shown. Infl uence of an economic situation on a role of these factors is allocated. For achievement of a sustainable development of the industrial enterprises it is off ered to realize measures for weakening of the factors resulting in economic instability.Conclusions / importance. In the conditions of new economic realities it is necessary to place emphasis on formation of economic policy of the state, directed on weakening of rate fl uctuation of national currency, stabilization of a bank rate of crediting, to reduction of prices of industrial and consumer goods, formation of the conditions promoting activization of business activity.